Characterization of the in vivo cardiac electrophysiologic effects of high-dose cocaine in closed-chest, anesthetized dogs with normal hearts - Fenelon,Guilherme (2003)
OBJECTIVE: To characterize the cardiac electrophysiologic effects of cocaine. METHODS: In 8 dogs (9-13 kg), electrophysiologic parameters and programmed stimulation were undertaken using transvenous catheters at baseline, and after cocaine intravenous infusion (12 mg/kg bolus followed by 0.22 mg/kg/min for 25 minutes). RESULTS: Cocaine plasma levels (n=5) rose to 6.73± 0.56 mg/mL. Cocaine did not affect sinus cycle length and arterial pressure. Cocaine prolonged P wave duration (54±6 vs 73±4 ms, P<0.001), PR interval (115±17 vs 164±15 ms, P<0.001), QRS duration (62±10 vs 88±14 ms, P<0.001), and QTc interval (344±28 vs 403±62 ms, P=0.03) but not JT interval (193±35 vs 226±53 ms, NS). Cocaine prolonged PA (9±6 vs 23±8 ms, P<0.001), AH (73±16 vs 92±15 ms; P=0.03), and HV (35±5 vs 45±3ms; P<0.001) intervals and Wenckebach point (247±26 vs 280±28 ms, P=0.04). An increase occurred in atrial (138±8 vs 184± 20 ms; P<0.001) and ventricular (160±15 vs 187±25 ms; P=0.03) refractoriness at a cycle length of 300 ms. Atrial arrhythmias were not induced in any dog. Ventricular fibrillation (VF) was induced in 2/8 dogs at baseline and 4/8 dogs after cocaine. CONCLUSION: High doses of cocaine exert significant class I effects and seem to enhance inducibility of VF but not of atrial arrhythmias.